Time domain analyses for three-phase lines with corrected modal transformation matrix - Prado, A. J. [UNESP]; Kurokawa, S. [UNESP]; Costa, E. C.M.; Filho, J. Pissolato; Bovolato, L. F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The results presented in this paper are based on a research about the application of approximated transformation matrices for electromagnetic transient analyses and simulations in transmission lines. Initially, it has developed the application of a single real transformation matrix for a double three-phase transmission lines, because the symmetry of the distribution of the phase conductors and the ground wires. After this, the same type of transformation matrix has applied for symmetrical single three-phase transmission lines. Analyzing asymmetrical single three-phase lines, it has used three different line configurations. For these transmission line types, the errors between the eigenvalues and the approximated results, called quasi modes, have been considered negligible. On the other hand, the quasi mode eigenvalue matrix for each case was not a diagonal one. And the relative values of the off-diagonal elements of the approximated quasi mode matrix are not negligible, mainly for the low frequencies. Based on this problem, a correction procedure has been applied for minimizing the mentioned relative values. For the correction procedure application, symmetrical and asymmetrical single three-phase transmission line samples have been used. Checking the correction procedure results, analyses and simulations have been carried out in mode and time domain. In this paper, the last results of mentioned research are presented and they related to the time domain simulations. © 2012 IEEE.
Keywords: Clarke's matrix; eigenvalue; eigenvector; error analysis; frequency dependent parameters; non symmetrical lines; phase mode transformation